Quantifying Intermodal Distraction by Emotion During Math Performance: An Electrophysiological Approach - Heim, Sabine; Keil, Andreas (Frontiers in Psychology, 2019)
Emotionally engaging stimuli are powerful competitors for limited attention capacity. In the cognitive neuroscience laboratory, the presence of task-irrelevant emotionally arousing visual distractors prompts decreased performance and attenuated brain responses measured in concurrent visual tasks. The extent to which distraction effects occur across different sensory modalities is not yet established, however. Here we examined the extent and time course of competition between a naturalistic distractor sound and a visual task stimulus, using dense-array electroencephalography (EEG) recordings from 20 college students. Steady-state visual evoked potentials (ssVEPs) were quantified from EEG, elicited by periodically flickering vignettes displaying basic arithmetic problems—the participants’ primary task. Concurrently, low-arousing and high-arousing sounds were presented, as well as auditory pink noise, used as a control. Capitalizing on the temporal dynamics of the ssVEP signal allowed us to study intermodal interference of the sounds with the processing of the visual math problems. We observed that high-arousing sounds were associated with diminished visuocortical responses and poor performance, compared to low-arousing sounds and pink noise, suggesting that emotional distraction acts across modalities. We discuss the role of sensory cortices in emotional distraction along with implications for translational research in educational neuroscience.